Effect of intermittent infusion hemodiafiltration on cerebral and hepatic oxygenation - Susumu Ookawara; Kiyonori Ito; Kazuma Fukuda; Tomoko Iida; Kazumi Yahagi; Haruhisa Miyazawa; Keiji Hirai; Mamoru Yoshizawa; Yoshiyuki Morishita (Renal Replacement Therapy)
Abstract Background Hepatosplanchnic circulation plays a crucial role in maintaining hemodynamic stability during hemodialysis (HD). In patients undergoing HD, hepatic oxygenation decreases before the onset of intradialytic hypotension. However, clinical studies comparing systemic tissue oxygenation, particularly in the brain and liver, between HD and intermittent infusion hemodiafiltration (I-HDF) are limited. We aimed to compare changes in the cerebral and hepatic oxygenation during I-HDF and HD. Methods This single-center prospective observational study included 25 patients undergoing dialysis therapy. I-HDF involved a dialysate infusion volume of 200 mL, administered at a rate of 150 mL/min via back-filtration every 30 min. Cerebral and hepatic regional oxygenation saturation (rSO2) levels were monitored during HD and I-HDF using the INVOS 5100C oxygen saturation monitor. Changes in these parameters were compared between the two modalities. Results The relative blood volume change (%ΔBV) at the end of therapy was significantly smaller with I-HDF compared with HD (−8.0 ± 4.4% versus −10.0 ± 5.0%, p = 0.019). No significant differences in cerebral and hepatic rSO2 were observed at the initiation of HD and I-HDF (cerebral rSO2: 54.5 ± 6.3% versus 54.0 ± 6.0%, p = 0.444; hepatic rSO2: 63.4 ± 11.8% versus 63.4 ± 12.3%, p = 0.977). During I-HDF, cerebral and hepatic rSO2 levels significantly increased in response to dialysate infusion, compared with corresponding time points during HD. The percentage (%) change in hepatic rSO2 after the seventh dialysate infusion was significantly greater than those after the first, third, and fifth infusions. Additionally, percentage changes in hepatic rSO2 were negatively correlated with %ΔBV (ρ = −0.394, p < 0.001) and positively correlated with the ratio of the dialysate infusion volume to circulating BV just before infusion (ρ = 0.387, p < 0.001). Conclusions This study demonstrated that BV reduction at the end of I-HDF was significantly smaller than that of HD, and that hepatic oxygenation increased rapidly after dialysate infusion during I-HDF. Further studies are required to elucidate the impact of increased hepatic oxygenation during I-HDF on intradialytic hemodynamic stability.